ASYMPTOTIC BEHAVIOR OF EIGENVALUES IN DISCRETE SCHRÖDINGER OPERATORS WITH POINT INTERACTION POTENTIAL (Innovations in Science and Technologies, 2025)
We investigate the one-particle discrete Schrödinger operator with Dirac delta potential on the -dimensional cubic lattice. We show that the operator the operator has a unique eigenvalue and obtain an asymptotics expansion for this eigenvalue as wight of potential approaches the infinity.